PERILAKU PEGAWAI PADA BIRO ORGANISASI SEKRETARIAT DAERAH KALIMANTAN BARAT - Anita E.21108115 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The success of an organization in achieving its goals can not be separated from the behavior of employees who interact in it. Behavior of employees is determined by many factors, among others, influenced by the capabilities, needs, or by the hope and the environment. The focus of this study refers to the main factors forming the individual or employee behavior such as attitudes, skills, and motivation of employees in the work. In discussing the focus of the study, used qualitative research methods with a case study conducted at the Biro Organisasi Sekretariat Daerah Kalimantan Barat. Based on the results of the study found that the ability of some employees still inadequate. This is because some employees have not gotten a chance to take part in education and training aimed at improving the ability of employees. Therefore, researchers suggest in order to improve work attitude, commitment, and job satisfaction of employees should be given an award for employees who have shown good performance. Leaders are expected to provide education and training to all employees to improve their ability to work. In addition, it is expected that leaders can give attention and appreciation to its employees to be motivated to work properly.Keywords: Apparatus Behavior, Employee Attitudes, Employee Ability, Motivation Employee.